Educational reinforcement measures in literacy: the case of the Dyslexia Aid program in the Comunidad de Madrid - Sevilla, Almudena; Cuevas Ruiz, Pilar; Sanz, Ismael; Rello, Luz (Gobierno de Espana Secretaria de Estado de Comercio, 2021)
In this article,we evaluate the Dyslexia Aid program of the Community of Madrid in the 2018-2019 academic year,aimed at primary school students with reading and writing difficulties. The program consists of two tools: a) a test to check students who have literacy difficulties and b) up to 42,000 exercises on a digital platform to work and reinforce these skills. 7.55 % (n = 1,022) of the students had reading and writing difficulties. The results of the analysis show that there is no correlation between the participation of the school in the program and the performance of the students at these schools in the external and standardized tests of Mathematics and Language,but there is in the case of English. When disaggregating the results by gender,a strong and positive association of the Dyslexia Help project is observed for girls in Language arts and English (and,as one might expect,not so much in Mathematics),while for boys it is only significant in English. However,schools that participate in this intervention have better results and students from a higher socio-economic background. The different characteristics of the schools could explain their participation,which was voluntary,in the Dyslexia Aid program. The future line of research proposes to exploit through a differences-in-differences analysis that there has been a new call for the program in the 2021-2022 academic year,in which new schools have been incorporated. © 2021,Gobierno de Espana Secretaria de Estado de Comercio. All rights reserved.
[Medidas educativas de refuerzo en lectoescritura: el caso del programa de Ayuda a la Dislexia en la Comunidad de Madrid]
Keywords: dyslexia; education; public programmes; remedial education; dyslexia; education; public programmes; remedial education